2016
DOI: 10.1111/ijfs.13265
|View full text |Cite
|
Sign up to set email alerts
|

Lipid oxidation of brown rice stored at different temperatures

Abstract: Summary Changes in lipid oxidation and quality of brown rice stored at different temperatures were investigated. Fatty acid value (FAV), peroxide value (POV) and carbonyl value (CV) of brown rice were determined every 45 day for 270 day. Volatile compounds in seven samples stored for 0, 135 and 270 day were also identified. Relationships between volatile compounds and oxidative indices were analysed. Results revealed that the FAV, POV and CV of brown rice significantly increased (P < 0.05) with prolonged stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…Liu, Li, et al. () observed considerable losses for Mg, Mn, Fe, and Pb during milling (DOM = 9%; Table ). These results indicated that the variation in the loss of elements were both associated with the DOM and rice genotypes.…”
Section: Effects Of Milling On Rice Grain Qualitymentioning
confidence: 97%
See 3 more Smart Citations
“…Liu, Li, et al. () observed considerable losses for Mg, Mn, Fe, and Pb during milling (DOM = 9%; Table ). These results indicated that the variation in the loss of elements were both associated with the DOM and rice genotypes.…”
Section: Effects Of Milling On Rice Grain Qualitymentioning
confidence: 97%
“…Liu, Li, et al. () showed that the content of crude lipid decreased from 2.43 to 2.86 g/100g to 0.60 to 0.60 g/100 mg with increased DOM from 0 to 15% (Table ). Monks et al.…”
Section: Effects Of Milling On Rice Grain Qualitymentioning
confidence: 97%
See 2 more Smart Citations
“…Bryant and McClung () evaluated the volatile profile of nine rice cultivars and eight of them exhibited hexanal prior to storage, demonstrating that lipid breakdown products can be quickly produced after harvest and that this is a cultivar‐dependent phenomenon. Liu, Li, Chen, and Yong () showed that when rice is stored at 15ºC, there is a delay of the oxidative rancidity of rice during long‐term storage, compared to 25 and 35ºC, but the type of synthesized volatiles is similar.…”
Section: Resultsmentioning
confidence: 99%